Chapter 3  Section B  NonNumerical Solutions
3.2
Differentiate Eq. (3.2) with respect to
P
and Eq. (3.3) with respect to
T
:
µ
∂β
∂
P
¶
T
=−
1
V
2
µ
∂
V
∂
P
¶
T
µ
∂
V
∂
T
¶
P
+
1
V
µ
∂
2
V
∂
P
∂
T
¶
=
βκ
+
µ
∂
2
V
∂
P
∂
T
¶
µ
∂κ
∂
T
¶
P
=
1
V
2
µ
∂
V
∂
T
¶
P
µ
∂
V
∂
P
¶
T
−
1
V
µ
∂
2
V
∂
T
∂
P
¶
=−
βκ
−
µ
∂
2
V
∂
P
∂
T
¶
Addition of these two equations leads immediately to the given equation.
One could of course start with Eq. (3.4) and apply the condition for an exact differential, but this topic
is not covered until Chapter 6.
3.3
The Tait equation is given as:
V
=
V
0
µ
1
−
AP
B
+
P
¶
where
V
0
,
A
, and
B
are constants. Application of Eq. (3.3), the definition of
κ
, requires the derivative
of this equation:
µ
∂
V
∂
P
¶
T
=
V
0
·
−
A
B
+
P
+
AP
(
B
+
P
)
2
¸
=
AV
0
B
+
P
µ
−
1
+
P
B
+
P
¶
Multiplication by
−
1
/
V
in accord with Eq. (3.3), followed by substitution for
V
0
/
V
by the Tait equa
tion leads to:
κ
=
AB
(
B
+
P
)
[
B
+
(
1
−
A
)
P
]
3.7
(
a
) For constant
T
, Eq. (3.4) becomes:
dV
V
=−
κ
dP
Integration from the initial state (
P
1
,
V
1
) to an intermediate state (
P
,
V
) for constant
κ
gives:
ln
V
V
1
=−
κ(
P
−
P
1
)
Whence,
V
=
V
1
exp[
−
κ(
P
−
P
1
)
]
=
V
1
exp
(
−
κ
P
)
exp
(κ
P
1
)
If the given equation applies to the process, it must be valid for the initial state; then,
A
(
T
)
=
V
1
exp
(κ
P
1
)
, and
V
=
A
(
T
)
exp
(
−
κ
P
)
(
b
) Differentiate the preceding equation:
dV
=−
κ
A
(
T
)
exp
(
−
κ
P
)
dP
Therefore,
W
=−
Z
V
2
V
1
PdV
=
κ
A
(
T
)
Z
P
2
P
1
P
exp
(
−
κ
P
)
dP
=
A
(
T
)
κ
[
(κ
P
1
+
1
)
exp
(
−
κ
P
1
)
−
(κ
P
2
+
1
)
exp
(
−
κ
P
2
)
]
545
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentWith
V
1
=
A
(
T
)
exp
(
−
κ
P
1
)
and
V
2
=
A
(
T
)
exp
(
−
κ
P
2
)
, this becomes:
W
=
1
κ
[
(κ
P
1
+
1
)
V
1
−
(κ
P
2
+
1
)
V
2
]
or
W
=
P
1
V
1
−
P
2
V
2
+
V
1
−
V
2
κ
3.11
Differentiate Eq. (3.34c) with respect to
T
:
T
µ
1
−
δ
δ
¶
P
[
(
1
−
δ)/δ
]
−
1
dP
dz
+
P
(
1
−
δ)/δ
dT
dz
=
T
µ
1
−
δ
δ
¶
P
(
1
−
δ)/δ
P
dP
dz
+
P
(
1
−
δ)/δ
dT
dz
=
0
Algebraic reduction and substitution for
dP
/
dz
by the given equation yields:
T
P
µ
1
−
δ
δ
¶
(
−
M
ρ
g
)
+
dT
dz
=
0
For an ideal gas
T
ρ/
P
=
1
/
R
. This substitution reduces the preceding equation to:
dT
dz
=−
M
g
R
µ
δ
−
1
δ
¶
3.12
Example 2.12 shows that
U
2
=
H
0
. If the gas is ideal,
H
0
=
U
0
+
P
0
V
0
=
U
0
+
RT
0
and
U
2
−
U
0
=
RT
0
For constant
C
V
,
U
2
−
U
0
=
C
V
(
T
2
−
T
0
)
and
C
V
(
T
2
−
T
0
)
=
RT
0
Whence,
T
2
−
T
0
T
0
=
R
C
V
=
C
P
−
C
V
C
V
When
C
P
/
C
V
is set equal to
γ
, this reduces to:
T
2
=
γ
T
0
This result indicates that the final temperature is independent of the amount of gas admitted to the
tank, a result strongly conditioned by the assumption of no heat transfer between gas and tank.
3.13 Isobaric case
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '10
 brown
 Trigraph, NC

Click to edit the document details